The Impact of State-of-the-Art Supply Chain Management Practices on Operational Performance - Althaqafi, Torky (ExcelingTech, 2020)
This study will investigate the impact of optimal supply chain practices on the operational performance of companies. To achieve its objectives, the study used a descriptive analytical method drawing on a desktop survey of the relevant literature on supply chain management and its impact on operational performance. The study analysed a number of research studies in the field of supply chains over the period 2010-2019.The study reached a number of conclusions, the most important of which is: the significant potential effects of supply chain management in improving the operational performance of enterprises. In light of the findings of the study, a number of recommendations are made: that organizations adopt a more strategic approach to supply chain management based on establishing strong, long-term relationships with suppliers, and customers, effective communications, so raising the standards and quality of sustainable business performance, and strengthening the connections between the three elements of the supply chain along with greater attention to the practices connected to relationships with customers.